Hypoxic storage of red blood cells improves metabolism and post‐transfusion recovery. Issue 4 (27th February 2020) - DʼAlessandro, Angelo; Yoshida, Tatsuro; Nestheide, Shawnagay; Nemkov, Travis; Stocker, Sarah; Stefanoni, Davide; Mohmoud, Fatima; Rugg, Neeta; Dunham, Andrew; Cancelas, Jose A.
Abstract : BACKGROUND: Blood transfusion is a lifesaving intervention for millions of recipients worldwide every year. Storing blood makes this possible but also promotes a series of alterations to the metabolism of the stored erythrocyte. It is unclear whether the metabolic storage lesion is correlated with clinically relevant outcomes and whether strategies aimed at improving the metabolic quality of stored units, such as hypoxic storage, ultimately improve performance in the transfused recipient. STUDY DESIGN AND METHODS: Twelve healthy donor volunteers were recruited in a two‐arm cross‐sectional study, in which each subject donated 2 units to be stored under standard (normoxic) or hypoxic conditions (Hemanext technology). End‐of‐storage measurements of hemolysis and autologous posttransfusion recovery (PTR) were correlated to metabolomics measurements at Days 0, 21, and 42. RESULTS: Hypoxic red blood cells (RBCs) showed superior PTR and comparable hemolysis to donor‐paired standard units. Hypoxic storage improved energy and redox metabolism (glycolysis and 2, 3‐diphosphoglycerate), improved glutathione and methionine homeostasis, decreased purine oxidation and membrane lipid remodeling (free fatty acid levels, unsaturation and hydroxylation, acyl‐carnitines). Intra‐ and extracellular metabolites in these pathways (including some dietary purines) showed significant correlations with PTR and hemolysis, though the degree of correlation was influenced by sulfur dioxide (SO2 ) levels. CONCLUSION: Hypoxic storage improves energy and redox metabolism of stored RBCs, which results in improved posttransfusion recoveries in healthy autologous recipients—a Food and Drug Administration gold standard of stored blood quality. In addition, we identified candidate metabolic predictors of PTR for RBCs stored under standard and hypoxic conditions.